The Impact of Teaching according to Online Survey Communities on the Communication Skills of First-Grade Female Students - Roua Qasim Waheed Al-Nayli; Dr. Nepal Abbas Hadi Al-Mahja (Migration Letters, 2023)
The current research aims to identify the impact of teaching according to the online survey communities on the communication skills of first-intermediate-grade students. Therefore, the researcher formulated the research hypothesis: "There is no statistically significant difference at the level of significance (0.05) between the mean scores of the students of the experimental group who will study according to the online survey communities and the average scores of the students of the control group who will study in the usual way in the communication skills scale." The current research identifies female students in the first intermediate grade in government day schools affiliated with the Directorate of Education of Al-Qadisiyah and the subject of science (the last four chapters) from the science book curriculum scheduled for the academic year 2022/2023 for the first intermediate grade. The researcher chose the experimental design with partial control (the experimental group and the group control) with a post-test for achievement, and a medium (Al-Rahma for Girls) was selected in a simple random way to represent the sample of the current research, and two divisions were chosen from the first intermediate grade of (74) students in a random manner, for each division (37) students, as division ( A) an experimental group and division (b) a control group, and the researcher equalized the two groups of the current research in the variables (chronological age and intelligence, and the communication skills scale), and the researcher also prepared the study tool, represented by preparing the communication skills scale, which consists in its final form of (40) items On (six skills) with (eight items) for speaking skills, (seven items) for listening skill, (five items) for writing skill, (seven items) for reading skill, (eight items) for visual non-verbal communication skill, and (five items) for skill Audio non-verbal communication, apparent validity, content validity and reliability were verified for this tool. The researcher applied the experiment in the second semester of the academic year 2022/2023. The experiment lasted (eight) weeks, and the data was analyzed and processed using the statistical analysis package for social sciences (SPSS) and the program (Microsoft Excel) by using the t-test for two independent samples and coefficient effect size. The researcher reached the following results: The result related to the research hypothesis of the results of the communication skills scale indicated that there were statistically significant differences between the mean scores of the students of the experimental group who studied the science subject in the survey communities via the Internet and the mean scores of the students of the control group who studied the same subject in the usual way in the variable of thinking skills in favour of the students of the experimental group.